The Impact of Product’s Color on Consumer Response to Visual Aesthetics: A Field Study on Consumers in Saudi Arabia - Badghish, Saeed; Alaslani, Razan (The Arab Journal of Administration, 2020)
This study aims to identify consumer trends toward some colors. It identifies the most influential factor in consumer response to aesthetics and how they are important to marketing activities. This research identifies the color preferences as well as the importance of color for respondents to search for different demographic characteristics. This helps to explore the impact of the visual aesthetics of colored product on consumers. In addition, it identifies the relationship between color and visual aesthetics of goods and their effect on consumer response. The research literature related to colors and its influences in aesthetics have been reviewed in this research. The study has adopted the descriptive analytical research as being appropriate to the nature and objectives of the study. Random sample data of 625 surveys have been gathered from the community of Saudi Arabia, where the study was applied, using the online questionnaire as a tool to collect the required data, and analyzed by SPSS statistical program. The study found that the color appearance of the product is considered as the main factor of consumers responses to products. There are statistically significant differences in the respondents’ preference of products colors. However, there is no significant difference between the importance of color to consumers according to gender. The study concluded that the color of the product raises consumer response towards visual aesthetics. So, this research recommends that marketers have to invest for exterior appearance of the product in order to increase the possibility of the product being selected in the consumer purchasing process due to its influential factors on consumer response.